Evaluation of the patency rate and endothelialization of a poly-ε-caprolactone, nanofiber sheet-based vascular graft using a rat abdominal aortic implantation model - Kikuchi, Yuta; Wakabayashi, Naohiro; Braghirolli, Daikelly I.; Pranke, Patricia; Kamiya, Hiroyuki; Oyama, Kyohei (Frontiers in Surgery, 2024)
IntroductionThe global increase in cardiovascular diseases has resulted in an augmented development of artificial small-caliber vascular grafts used in bypass graft surgeries, such as coronary and distal artery bypass graft surgeries. However, no consensus exists regarding the best method for creating vascular grafts. Poly-ε-caprolactone (PCL) is a biocompatible and biodegradable material that has been widely studied as a scaffold for tissue regeneration, inclusive of vascular grafts. In this study, a vascular graft was created from a PCL nanofiber sheet (PCL graft), and the performance thereof was examined using a rat abdominal aortic implantation model.MethodsThe PCL nanofiber sheets were created using an electrospinning machine. These nanofiber sheets were rolled up. Glue was applied between layers using a PCL solution to create a PCL nanofiber vascular graft, with an inner diameter of 1 mm. PCL grafts with 7 mm length were implanted into the abdominal aorta of rats. Thereafter, the patency was determined by pulsating blood flow from the hemiresection site of the distal aorta of the graft anastomosis, and endothelialization was examined using hematoxylin and eosin and immunofluorescent staining methods.ResultsThe patency rate of the PCL graft at 2 weeks was 57.1% (12 of 21 cases), which is not satisfactory as a small-caliber vascular graft. Patent cases, however, revealed a CD31-positive endothelial cell layer in the inner lumen and autologous cell infiltration into the scaffold, indicating autologous vessel-like regeneration. By contrast, the occluded cases showed disassembly of the nanofiber layers; and the inner layers folded into the middle of the lumen. This observation suggested that the disassembled inner layer of the PCL graft disturbed the blood flow and triggered occlusion.ConclusionsPCL grafts can exhibit autologous vessel-like regeneration; nonetheless, regarding patency, grafts made from rolled-up PCL nanofiber sheets have structural weaknesses. Further improvements are required to achieve a long-term and high patency rate for PCL grafts.